Fuzzy logic gain scheduling for non-linear servo tracking - Brdyś, Mieczysław A.; Littler, Jonathan J. (Zielona Góra: Uniwersytet Zielonogórski)
This paper proposes the use of gain scheduling as a method of controlling a servo system with hard non-linear elements. The servo controls two elements of a tracker mounted on a ship at sea. There is stiction at the zero velocity point and non-linear friction against the motion of each tracker axis. A dual feedback loop control structure is employed.
Keywords: tracking; servo control; gain scheduling; fuzzy logic; stiction friction; hard non-linearities